2003
DOI: 10.1124/jpet.103.053306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Profile of Vasodilation by CVT-3146, a Novel A2A Receptor Agonist, and Adenosine in Conscious Dogs

Abstract: The purpose of this study was to determine the magnitude of vasodilation by CVT-3146 in different vascular beds and to compare it with that by adenosine in conscious dogs. Intravenous bolus injections of CVT-3146 (0.1-2.5 g/kg) or adenosine (10 -250 g/kg) caused a dose-dependent increase in the coronary blood flow (CBF) and a dose-dependent decrease in the late diastolic coronary resistance. Although the maximal increase in CBF response to the two drugs was not significantly different, the ED 50 of CVT-3146 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 24 publications
(36 reference statements)
2
45
1
Order By: Relevance
“…18 In another study of conscious dogs, IV regadenoson (0.1-2.5 lg/kg) or adenosine (10-250 lg/kg) caused similar dose-dependent increases in CBF and dose-dependent decreases in the late diastolic coronary resistance. 19 Regadenoson at 2.5 lg/kg caused a similar increase in maximal CBF compared to 250 lg/kg of adenosine though the increase in CBF was significantly of longer duration with regadenoson ( Figure 4). 19 Adenosine (ED50 = 47 ± 7.77 lg/kg) was 100 times less potent than regadenoson (ED50 = 0.45 ± 0.07 lg/kg).…”
Section: Coronary Vasodilatationmentioning
confidence: 75%
See 1 more Smart Citation
“…18 In another study of conscious dogs, IV regadenoson (0.1-2.5 lg/kg) or adenosine (10-250 lg/kg) caused similar dose-dependent increases in CBF and dose-dependent decreases in the late diastolic coronary resistance. 19 Regadenoson at 2.5 lg/kg caused a similar increase in maximal CBF compared to 250 lg/kg of adenosine though the increase in CBF was significantly of longer duration with regadenoson ( Figure 4). 19 Adenosine (ED50 = 47 ± 7.77 lg/kg) was 100 times less potent than regadenoson (ED50 = 0.45 ± 0.07 lg/kg).…”
Section: Coronary Vasodilatationmentioning
confidence: 75%
“…19 Regadenoson at 2.5 lg/kg caused a similar increase in maximal CBF compared to 250 lg/kg of adenosine though the increase in CBF was significantly of longer duration with regadenoson ( Figure 4). 19 Adenosine (ED50 = 47 ± 7.77 lg/kg) was 100 times less potent than regadenoson (ED50 = 0.45 ± 0.07 lg/kg). 19 Regadenoson (2.5 lg/kg IV bolus) and adenosine (4.5-minute infusion at 280 lg/kg) were studied in anesthetized dogs.…”
Section: Coronary Vasodilatationmentioning
confidence: 75%
“…The observed lack of effect of the adenosine analogue regadenoson on the diameter of retinal arterioles may potentially be due to a too low concentration of the compound for a vasoactive effect to have been elicited. Although the employed concentration of regadenoson can affect coronary function [8, 19], the sensitivity of retinal arterioles to the compound may be lower than that of arterioles in the systemic circulation [20]. Previous studies have shown that adenosine has affinity to a number of adenosine receptor types [21] and that the dilating effect of the compound requires functional Na-K pumps and K ATP channels [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of conscious dogs, Zhao et al [10] measured the magnitude of vasodilation by regadenoson and adenosine in different vascular beds. The maximal increase in CBF response to the two drugs was similar, but the potency of regadenoson and adenosine was markedly different.…”
Section: Selectivity For A2amentioning
confidence: 99%